Buddhist Integration to Promote the Quality of Working Life in the Performances Personnel, Nan Public Health Office - Kunchum, Piyada; Suklueang, Kiettisak (Journal of Thammawat, 2024)
The purpose of this article was: 1) to study the quality of working life of personnel under the Nan Provincial Public Health Office, 2) to study the relationship between the principles of Iddhipatthamma and the quality of working life of personnel under the Nan Provincial Public Health Office, 3) to present a Buddhist integration for promoting the quality of working life of personnel under the Nan Provincial Public Health Office based on the principles of Iddhipatthamma. This was mixed methods research. Data was collected from a sample of 363 people. Descriptive data analysis used frequency, percentage, mean, and standard deviation. The relationship was analyzed using Pearson's correlation coefficient. In-depth interviews were conducted with 9 key informants. Data was analyzed using content summary techniques to present guidelines. The results showed that the overall quality of working life of personnel under the Nan Provincial Public Health Office was at a high level. There was a moderately positive relationship between the principles of Iddhipatthamma and the quality of working life of the personnel (r = 0.527) at a statistical significance level of 0.01. Regarding the Buddhist integration to promote the quality of working life based on the Factors of Accomplishment, it was found that applying the principles of Iddhipatthamma to enhance work efficiency and improve work performance necessitates interrelating the prominent principles of each factor. This will lead to efficient work performance of the personnel and greatly benefit the organization in developing its personnel's work capabilities. The principles of Iddhipatthamma aim to create a mental state, then arouse and reinforce it, leading to the arising of concentration with strength to enable joyful and successful work.